Pengembangan E-Handout Berbasis Android Dengan Model PBL Untuk Meningkatkan Keterampilan Metakognitif Siswa - Lupita Ratna Sari; Ali Usman; Agus Prasetyo Utomo (Smart Education, 2024)
Abstract: In education, learning activities that combine learning media with learning models are very suitable for improving student learning outcomes. This research aims to develop Android-based biology e-handout learning media for coordination system material using the Problem-Based Learning (PBL) model to improve students' meta-cognitive skills in high school. This type of research is research and development (R&D) with the 4D (Four D) research model. The learning media developed is then tested for suitability through product validity and trials. Based on the research results, the biology e-handout learning media is valid, with an assessment percentage calculation of 97.5% by linguists, 78.12% by media experts, 93.42% by material experts, and 93.42% by high school biology teachers. The category is very suitable for use in learning. The e-handout learning media that has been developed is proven to be able to improve students' metacognitive skills with a gain score of 0.76 and a percentage increase in student learning skills after using e-handouts of 76%, which means that e-handout learning media has a high level of effectiveness in improving student's metacognitive skills.Keywords: e-handout, metacognitive skills, problem-based learningÂ Â Abstrak: Pada dasarnya dalam dunia pendidikan kegiatan pembelajaran yang menggabungkan media pembelajaran dengan model pembelajaran sangat cocok untuk meningkatkan hasil belajar siswa. Tujuan penelitian ini adalah mengembangkan media pembelajaran e-handout biologi berbasis android materi sistem koordinasi dengan model Problem Based Learning (PBL) untuk meningkatkan keterampilan metakognitif siswa di SMA. Jenis penelitian ini adalah penelitian dan pengembangan atau Research and Development (R&D) dengan model penelitian 4D (Four D). Media pembelajaran yang dikembangkan kemudian diuji kelayakannya dengan validitas dan uji coba produk. Berdasarkan hasil penelitian media pembelajaran e-handout biologi sudah valid dengan perhitungan presentase penilaian sebesar 97,5% oleh ahli bahasa, 78,12% oleh ahli media, 93,42% oleh ahli materi dan 93,42% oleh guru biologi SMA dengan kategori sangat layak digunakan dalam pembelajaran. Media pembelajaran e-handout yang telah dikembangkan terbukti dapat meningkatkan keterampilan metakognitif siswa dengan nilai gain score yang diperoleh 0,76 dengan presentase peningkatan keterampilan belajar siswa setelah menggunakan e-handout sebesar 76% yang berarti media pembelajaran e-handout memiliki tingkat keefektifan yang tinggi dalam meningkatkan keterampilan metakognitif siswa.Kata kunci: e-handout, keterampilan metakognitif, problem based learning